POSITIVE POLITENESS STRATEGIES IN MIDNIGHT IN PARIS MOVIE BY WOODY ALLEN - Permadi, Wirdah Amaliyah (Universitas Gunadarma, 2018)
This study is an analysis of positive politeness strategies in Midnight in Paris movie by Woody Allen. The writer takes positive politeness strategies in a movie because the writer believes that people can learn pragmatics deeper through a movie and wants to see how the positive politeness strategies are employed in a movie through dialogues, since the writer also believes that understanding politeness is important. The aims of this study are to mention and describe the kinds of positive politeness strategies that are employed by the characters in Midnight in Paris movie and to explain the reasons that influence the characters to employ those strategies. This study uses qualitative method. The source of the data is taken from a Hollywood movie entitled Midnight in Paris by Woody Allen. The data is in the form of sentences which deal with utterances related to the positive politeness strategies. The data are utterances employed by the characters from the movie which indicate positive politeness strategies. The data are analyzed into kinds of positive politeness strategies. The writer finds that there are 13 positive politeness strategies in this movie from 50 data. Exaggerate (interest, approval, sympathy with H) strategy is the most dominant kind of positive politeness strategies employed by the characters in Midnight in Paris movie with 15 data, while both assert or presuppose knowledge of and concern for the hearer’s wants strategy and give gifts to H (goods, sympathy, understanding, cooperation) strategy are the lowest with only 1 datum of each strategy.